SUFISME PERKOTAAN DAN PEDESAAN DI ERA MODERNISASI DAN SEKULARISASI - Andarwati, Lilis (UNIVERSUM, 2016)
Islam freed adherents make a selection from the church in the search for his true identity in this world. The phenomenon of the excitement of urban and rural communities to the Islamic religion more real . Sufism or dhikr (Dzikir, wirid) is done in the form of doctrine, understanding and spiritual practices by individuals for the purpose of self-purification, in order to achieve the approach to the God (Kholiq). Sufism of urban intends to bring peace of mind, happiness, relief and satisfaction. Sufism of urban known modern times, it founded the middle of business meetings with a suit and tie of neatly. While, the Sufism of countryside only to worship the God (Khaliq) performed with a variety of dhikr (wirid) deeds for rural communities in the era of modernization and secularization are increasingly rational and secular.Keyword: Sufisme, Modernisasi, Sekularisasi